The double sides of hope: The meaning of hope among amyotrophic lateral sclerosis (ALS) patients. - Hamama-Raz, Yaira; Norden, Yair; Buchbinder, Eli (Death Studies, 2021)
Hope is an important factor in coping and adjusting to life-threatening disease. In this study, we examined the meaning of hope among people with amyotrophic lateral sclerosis (ALS). Semi-structured interviews with 12 people revealed that hope had two contradictory meanings. For some, hope was considered an obstacle to achieving control and to actively cope with the disease. Alternatively, other people with ALS regarded hope as a crucial resource, which empowered their coping and control. These findings are discussed in the context of research and theoretical literature about hope and coping processes.